Glass ceramic armour systems for light armour applications - Horsfall, Ian (Cranfield University, 2001)
This paper descries an experimental evaluation of lithium-zinc-silicate glass ceramics when used as the strike face of an armour system. It is shown that against soft cored 7.62mm rounds (lead or mild steel cores) glass ceramics offer protection at an areal density which is equal to or better than alumina faced systems. The lithium zinc silicate system has a relatively low hardness (Hv 600) when compared to conventional ceramics such as alumina (typically Hv1300-1500). Consequently the performance of the glass ceramic system against hard cored projectiles is poor.